Simulation strategies for wind shields and porous barriers for bridge deck optimization. (June 2022) - Xu, Mao; Patruno, Luca; Lo, Yuan-Lung; de Miranda, Stefano
Highlights: Bridge decks with porous wind barriers are studied using 2D-URANS. Simulations are performed modelling the barrier geometry and using pressure-jumps. Results obtained using the two approaches are compared with experimental data. Discrepancies are found to be related to the flow deflection at the barrier. Abstract: Wind shields and porous barriers are often positioned on bridge decks as ancillary structures. While being irrelevant from the structural point of view, it is well-known that their presence can deeply affect the deck aerodynamic performance. In particular, not only do they generally lead to an increase of the drag force, but also they modify the overall flow arrangement, so affecting all aerodynamic coefficients. In this paper, the numerical simulation of porous elements positioned on bridge sections is addressed following two approaches: in the first one, the pores are explicitly modeled, while in the second one a more convenient pressure-jump approach is adopted. In particular, the second approach has strong advantages compared to the first one, especially when simulations are used for optimization. The results obtained using these approaches are compared with each other and experimental measurements, highlighting strengths and limitations of both methodologies.